På kulturforskningens bakgårdar - Löfgren, Orvar; Ehn, Billy (Tidsskrift for kulturforskning, 2010)
In contemporary cultural studies there has been a marked focus on a modern world in flux and transformation. Life is often depicted in terms of an ever-increasing individualism and a constant fragmentation of social life and old collectives. This paper takes a critical look at this genre. What kinds of processes that create stability and continuity in people's lives are overlooked or ignored?  How can we develop analytical perspectives to capture such undercurrents in society? One such field is explored - that of everyday routines. The argument is that it is precisely their seemingly trivial and insignificant position that may make routines powerful in society